2001
DOI: 10.1016/s0885-3924(00)00243-8
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin in Phantom Limb Pain Management in Children and Young Adults

Abstract: Seven children and young adults with phantom limb pain (PLP) were treated with gabapentin. PLP resolved in six patients within two months. One patient still had symptoms to a lesser degree. Mean follow up time was 1.74 years. Gabapentin may be a useful adjunct to pain management in patients with PLP symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Because it does not appear to significantly affect hematopoiesis, gabapentin may be the drug of choice for children with cancer and NP. It has been used successfully in the treatment of phantom limb pain in adults (Bone, Critchley, & Buggy, 2002), children and adolescents (Bone, Critchley, & Buggy, 2002; Rusy, Troshynski, & Weisman, 2001) and for cancer-related NP in adults (Caraceni et al, 2004) and children (Jacob, 2004). Gabapentin has been in use for NP at St. Jude since 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Because it does not appear to significantly affect hematopoiesis, gabapentin may be the drug of choice for children with cancer and NP. It has been used successfully in the treatment of phantom limb pain in adults (Bone, Critchley, & Buggy, 2002), children and adolescents (Bone, Critchley, & Buggy, 2002; Rusy, Troshynski, & Weisman, 2001) and for cancer-related NP in adults (Caraceni et al, 2004) and children (Jacob, 2004). Gabapentin has been in use for NP at St. Jude since 1997.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing medical literature, it became evident that GBP and TGB are the efficacious drugs in reducing acute and chronic pain in the experimental models of nociception (Shimoyama et al, 1997;Hunter et al, 1997;Ipponi et al, 1999;Lu and Westlund, 1999;Laughlin et al, 2002). Moreover, some authors indicated the clinical efficacy of GBP in the treatment of pain neuropathy after herpes zoster (Rowbotham et al, 1998;Rice and Maton, 2001;Serpell et al, 2002), trigeminal neuralgia (Carrazana and Schachter, 1998), peripheral neuropathy in patients with diabetes (Backonja et al, 1998, Backonja, 1999, or phantom limb pain (Rusy et al, 2001). With respect to TGB, it has significantly reduced sensitive neuropathy in patients resistant to the standard antinociceptive therapy (Novak et al, 2001).…”
Section: Controlmentioning
confidence: 99%
“…Although tricyclic antidepressants and gabapentin are well-established analgesics for these conditions in adults, evidence for efficacy in children is confined to case reports or very small case series. 7,8 Only 1 randomized controlled trial on 28 children has been conducted to evaluate multimodal approaches for CRPS I. Lee et al showed that a 6-week course of cognitive-behavioral therapy combined with either 3 times weekly or once-weekly physiotherapy sessions reduced pain and disability in children. 9 Moreover, no study has yet evaluated what treatments work for those children and adolescents who do not respond to a multimodal treatment approach.…”
Section: Discussionmentioning
confidence: 99%